2014
DOI: 10.1016/j.drugalcdep.2014.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Modeling substance use in emerging adult gay, bisexual, and other YMSM across time: The P18 cohort study

Abstract: Objective To examine patterns of substance use over time in a new generation of emerging adult gay, bisexual, and other young men who have sex with men (YMSM). Methods Data were drawn from the first four waves of on ongoing prospective cohort study of YMSM who were ages 18 to19 at baseline and were assessed each 6 months for substance use via calendar based methods. Latent growth curve modeling was utilized to assess changes over time for four drug use categories: alcohol, marijuana, inhalant nitrates, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 48 publications
5
21
1
Order By: Relevance
“…Growth from the age of 22 to 24 was only significant for poly-drug use. Previous research has found evidence of increases in alcohol and drug use as YMSM move from adolescence to young adulthood (Dermody et al, 2014; Halkitis et al, 2014; Hatzenbuehler et al, 2008; Marshal et al, 2009; Newcomb et al, 2012), and these analyses expand on prior work and indicate that this growth may occur primarily during the teenage years. We also found that change for all three substance use behaviors was significantly positively correlated at both ages 17–21 and ages 22–24, with the exception of alcohol and poly-drug use which was only correlated at ages 17–21.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Growth from the age of 22 to 24 was only significant for poly-drug use. Previous research has found evidence of increases in alcohol and drug use as YMSM move from adolescence to young adulthood (Dermody et al, 2014; Halkitis et al, 2014; Hatzenbuehler et al, 2008; Marshal et al, 2009; Newcomb et al, 2012), and these analyses expand on prior work and indicate that this growth may occur primarily during the teenage years. We also found that change for all three substance use behaviors was significantly positively correlated at both ages 17–21 and ages 22–24, with the exception of alcohol and poly-drug use which was only correlated at ages 17–21.…”
Section: Discussionsupporting
confidence: 61%
“…Halkitis and colleagues (2014) followed YMSM at ages 18–19 for eighteen months and found that not only did YMSM increase in alcohol use over time, but that they also increased in marijuana and illicit drug use (defined in this study as cocaine, ecstasy, GHB, ketamine, heroin, rohypnol, and methamphetamine use) as well. These findings are in line with what has typically been found with heterosexual male populations (Chen and Kandel, 1995; Kandel and Logan, 1984).…”
Section: Introductionmentioning
confidence: 73%
“…Several factors were protective against SMY drug use including higher socioeconomic status [65], school connectedness [66], and higher self-esteem [67]. In fact, school enrollment itself predicted less past-3-month drug use in a predominantly Black and Latino SMY sample [68].…”
Section: Resultsmentioning
confidence: 99%
“…Black and Latino adolescent SMM were also more likely than Whites to report lifetime anabolic steroid use [59], a disparity that was associated with depressive symptomatology [58]. Asian young SMM reported decreasing rates of inhalant use over time, a finding not observed in other racial/ethnic groups [65]. Among Black SMY, race-based discrimination was also associated with adolescent HED and cannabis use [78].…”
Section: Resultsmentioning
confidence: 99%
“…The minority stress framework postulates that these patterns of psychosocial distress arise from the experience of discrimination, harassment, and stigma that occur as a result of social and institutional marginalization [15]. Many of the disparities found in sexual minority populations are attributed to minority stress [16].…”
Section: Introductionmentioning
confidence: 99%